Effective Factors on the Generated Transient Voltage in the Wind Farm due to Lightning - M. A. Abd-Allah; Mahmoud N. Ali; A. Said (Institute of Advanced Engineering and Science, 2015)
According to reports that had been published in many papers, wind turbines (WTs) fault due to lightning is one of the most difficult challenges. Lightning overvoltage lead to malfunction in the wind farm equipments. These improper functioning contain of malfunction electronic equipments and deformation of transformer winding and Surge arrester failures. The travelling waves which are generated due to high ground potential rise under lightning struck turbine cause these problems. To evaluate these cases, it must be performed an accurate analysis on the wave shape and level of the Lightning overvoltage and ground potential rise. This paper investigates the effective factors on the wave shape and level of the overvoltage, GPR and surge arrester burnout. These factors are included impulse Current-second characteristics, position of lightning, inception angle, multiple lightning strokes and chopped current. ATP-EMTP simulation program is applied to analyze the lightning over-voltage of onshore wind farm. This paper provides a practical procedure of lightning protection. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6844